Electrostatically actuated encased cantilevers - Desbiolles, Benoit X.E. (2018)
Background: Encased cantilevers are novel force sensors that overcome major limitations of liquid scanning probe microscopy. By trapping air inside an encasement around the cantilever, they provide low damping and maintain high resonance frequencies for exquisitely low tip-sample interaction forces even when immersed in a viscous fluid. Quantitative measurements of stiffness, energy dissipation and tip-sample interactions using dynamic force sensors remain challenging due to spurious resonances of the system. Results: We demonstrate for the first time electrostatic actuation with a built-in electrode. Solely actuating the cantilever results in a frequency response free of spurious peaks. We analyze static, harmonic, and sub-harmonic actuation modes. Sub-harmonic mode results in stable amplitudes unaffected by potential offsets or fluctuations of the electrical surface potential. We present a simple plate capacitor model to describe the electrostatic actuation. The predicted deflection and amplitudes match experimental results within a few percent. Consequently, target amplitudes can be set by the drive voltage without requiring calibration of optical lever sensitivity. Furthermore, the excitation bandwidth outperforms most other excitation methods. Conclusion: Compatible with any instrument using optical beam deflection detection electrostatic actuation in encased cantilevers combines ultra-low force noise with clean and stable excitation well-suited for quantitative measurements in liquid, compatible with air, or vacuum environments.